2017
DOI: 10.3390/molecules22121868
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the Anti-Oxidative Function of trans-Cinnamaldehyde-Included β-Cyclodextrin Complex

Abstract: trans-Cinnamaldehyde (tCIN), an active compound found in cinnamon, is well known for its antioxidant, anticancer, and anti-inflammatory activities. The β-cyclodextrin (β-CD) oligomer has been used for a variety of applications in nanotechnology, including pharmaceutical and cosmetic applications. Here, we aimed to evaluate the anti-inflammatory and antioxidant effects of tCIN self-included in β-CD complexes (CIs) in lipopolysaccharide (LPS)-treated murine RAW 264.7 macrophages. RAW 264.7 macrophages were treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 40 publications
(52 reference statements)
0
21
0
Order By: Relevance
“…Trans-cinnamaldehyde (tCA) is one of the major phytochemical constituents isolated from the stem bark of Cinnamomum cassia (L.) J. Presl (Cinnamon), which is frequently used in traditional medicine for the prevention and treatment of various diseases such as ischemia, anxiety, arrhythmia, indigestion, diabetes, gastritis, blood circulation disorders, and so on [18][19][20]. A number of previous studies have shown that tCA has a variety of beneficial pharmacological effects, including anti-inflammatory, antioxidant, anti-diabetic, anti-obesity, neuroprotective, and anti-tumor effects in a number of in vitro and in vivo models [21][22][23][24][25][26][27].…”
Section: Ivyspringmentioning
confidence: 99%
“…Trans-cinnamaldehyde (tCA) is one of the major phytochemical constituents isolated from the stem bark of Cinnamomum cassia (L.) J. Presl (Cinnamon), which is frequently used in traditional medicine for the prevention and treatment of various diseases such as ischemia, anxiety, arrhythmia, indigestion, diabetes, gastritis, blood circulation disorders, and so on [18][19][20]. A number of previous studies have shown that tCA has a variety of beneficial pharmacological effects, including anti-inflammatory, antioxidant, anti-diabetic, anti-obesity, neuroprotective, and anti-tumor effects in a number of in vitro and in vivo models [21][22][23][24][25][26][27].…”
Section: Ivyspringmentioning
confidence: 99%
“…There are few studies including these compounds and interactions with the NO/cGMP system. Davaatseren et al (18) recently reported that trans-cinnamaldehyde, an active compound of cinnamon did not affect the production of NO. In addition, the relaxation response to CA in rat aorta and porcine coronary artery did not alter in the presence of NOS and sGC inhibitors (19, 20).…”
Section: Discussionmentioning
confidence: 99%
“…Natural products from cinnamon plants ( Cinnamomum spp., Lauraceae) exhibit various bioactivities, such as antimicrobial, insecticidal, anti-inflammatory, antidiabetic activities and, etc. [ 1 , 2 , 3 , 4 , 5 ]. Cinnamomum osmophloeum Kanehira is commonly used as folk medicines and food flavors.…”
Section: Introductionmentioning
confidence: 99%